Promoting competition in the fertilizer industry and efficiency in the fertilizer use to improve land productivity and sustainability - Torero, Máximo; Hernandez, Manuel A. (T20 Argentina, 2018)
Given the central role that agriculture plays in the rural economy in developing countries, governments have implemented supply- and demand-side policies and programs to promote sustainable fertilizer use yielding mixed results. Policies typically have not addressed hurdles to fertilizer uptake emanating from highly concentrated fertilizer markets and the related lack of competitive pricing behavior among fertilizers producers and distributors. Fertilizer production worldwide is dominated by few producers. Most developing countries, especially in Africa, rely almost exclusively on imported fertilizer. Locally, fertilizer distribution channels are also characterized by a small number of market actors and poor dealer networks. As a result, fertilizers tend to be expensive and/or difficult to access for many farmers, limiting uptake. The G20 could play a transformative role in improving poor farmers’ access of fertilizers through three main channels: (1) establish a G20-led Global Task Force to Promote Fertilizer Trade and Uptake in developing countries, with special emphasis on Africa; (2) promote the formation of a consortium of multilateral and regional development banks for the creation of a financing facility for investments in new fertilizer plants to increase market competition and reduce fertilizer cost; and (3) mobilize financial support for the elaboration of open-access, detailed soil maps that identify soil classes and soil properties.